Integrity of Powdered and Powder-free Latex Examination Gloves - Andrew J. Calhoun, BS, MS; Gary E. Rodrick, PhD; Frederic H. Brown, DMD, MS (Blackwell Synergy, 2002)
The difference in permeability between one brand of powdered and another of powder-free latex examination gloves was evaluated to determine leak rates